Deficiency of N-linked glycosylation impairs immune function of B7-H6 - Chen, Hanqing; Zhang, Yang; Shen, Yu; Jiang, Liang; Zhang, Guangbo; Zhang, Xueguang; Xu, Yang; Fu, Fengqing (Frontiers in Immunology, 2023)
B7-H6 is a novel immune checkpoint molecule that triggers NK cell cytotoxicity, but the role of Nglycosylation in B7-H6 is poorly understood. We here identified the existence of N-glycosylation of B7-H6 in different cell lines and exogenous expression cells by PNGase F digestion and tunicamycin blockage. Subsequently, we demonstrated that B7-H6 contains 6 functional N-linked glycosylation sites by single site mutation and electrophoresis. Phylogenetical and structural analysis revealed that N43 and N208 glycan are conserved in jawed vertebrates and may thus contribute more to the biological functions. We further demonstrated that N43 and N208 glycosylation are essential for B7-H6 to trigger NK cell activation. Mechanistically, we found that N43 and N208 glycan contributed to the stability and membrane expression of B7-H6 protein. Lack of N208 glycosylation led to membrane B7-H6 shedding, while N43 mutation resulted in impaired B7-H6/NKp30 binding affinity. Together, our findings highlight the significance of N-linked glycosylation in B7-H6 biological functions and suggest potential targets for modulating NK cell-mediated immunity.